Systematic review of global hepatitis E outbreaks to inform response and coordination initiatives - Fatima H. Al-Shimari; Camerin A. Rencken; Carl D. Kirkwood; Ramya Kumar; Kirsten S. Vannice; Barclay T. Stewart (BMC, 2023)
Abstract Introduction Hepatitis E virus (HEV) is the most common cause of acute hepatitis. While symptoms are generally mild and resolve within weeks, some populations (e.g., pregnant women, immunocompromised adults) are at high-risk of severe HEV-related morbidity and mortality. There has not been a recent comprehensive review of contemporary HEV outbreaks, which limits the validity of current disease burden estimates. Therefore, we aimed to characterize global HEV outbreaks and describe data gaps to inform HEV outbreak prevention and response initiatives. Methods We performed a systematic review of peer-reviewed (PubMed, Embase) and gray literature (ProMED) to identify reports of outbreaks published between 2011 and 2022. We included (1) reports with ≥ 5 cases of HEV, and/or (2) reports with 1.5 times the baseline incidence of HEV in a specific population, and (3) all reports with suspected (e.g., clinical case definition) or confirmed (e.g., ELISA or PCR test) cases if they met criterium 1 and/or 2. We describe key outbreak epidemiological, prevention and response characteristics and major data gaps. Results We identified 907 records from PubMed, 468 from Embase, and 247 from ProMED. We screened 1,362 potentially relevant records after deduplication. Seventy-one reports were synthesized, representing 44 HEV outbreaks in 19 countries. The populations at risk, case fatalities, and outbreak durations were not reported in 66% of outbreak reports. No reports described using HEV vaccines. Reported intervention efforts included improving sanitation and hygiene, contact tracing/case surveillance, chlorinating boreholes, and advising residents to boil water. Commonly missing data elements included specific case definitions used, testing strategy and methods, seroprevalence, impacts of interventions, and outbreak response costs. Approximately 20% of HEV outbreaks we found were not published in the peer-reviewed literature. Conclusion HEV represents a significant public health problem. Unfortunately, extensive data shortages and a lack of standardized reporting make it difficult to estimate the HEV disease burden accurately and to implement effective prevention and response activities. Our study has identified major gaps to guide future studies and outbreak reporting systems. Our results support the development of standardized reporting procedures/platforms for HEV outbreaks to ensure accurate and timely data distribution, including active and passive coordinated surveillance systems, particularly among high-risk populations.